1999
DOI: 10.1086/314989
|View full text |Cite
|
Sign up to set email alerts
|

Avidity Maturation of Antibody toHaemophilus influenzaeType b (Hib) after Immunization with Diphtheria‐Tetanus–Acellular Pertussis–Hib–Hepatitis B Combined Vaccine in Infants

Abstract: Antibody avidity to Haemophilus influenzae type b (Hib) polysaccharide (PS) was assessed in infants vaccinated with diphtheria-tetanus-acellular pertussis (DTaP) combined with Hib-PS conjugated to tetanus toxoid (PRP-T) and hepatitis B (HB) (DTaP-PRP-T-HB) and after a PRP-conjugate (CRM197-OS) booster 3-7 months later. Avidity differed between infants with anti-Hib-PS IgG antibody <1 or >1 microg/mL postprimary series (avidity index [AI], 42%, 95% confidence interval [CI], 35%-49%, and 68% and 63%-72%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
4
17
0
Order By: Relevance
“…By examining avidity maturation following a 10-g booster dose of meningococcal polysaccharide, we have demonstrated that vaccinated individuals with SBA titers above and below 128 display similar avidity maturation in their antibody response and by this criterion should therefore have immunological memory established. Data now exist which demonstrate the increase in avidity over time following priming of infants or toddlers with Hib (18,30), Streptococcus pneumoniae (3), and Neisseria meningitidis serogroup C conjugate vaccines (31). Such data have been generated in the context of boosters of low doses of plain polysaccharide or conjugate vaccine in young infants and are now accepted as indicative that a T-celldependent response has been generated.…”
Section: Discussionmentioning
confidence: 99%
“…By examining avidity maturation following a 10-g booster dose of meningococcal polysaccharide, we have demonstrated that vaccinated individuals with SBA titers above and below 128 display similar avidity maturation in their antibody response and by this criterion should therefore have immunological memory established. Data now exist which demonstrate the increase in avidity over time following priming of infants or toddlers with Hib (18,30), Streptococcus pneumoniae (3), and Neisseria meningitidis serogroup C conjugate vaccines (31). Such data have been generated in the context of boosters of low doses of plain polysaccharide or conjugate vaccine in young infants and are now accepted as indicative that a T-celldependent response has been generated.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a critical point with regard to the extension of early life immunization strategies is to ensure the quality of induced responses and the duration of protection. Recently, it has been demonstrated that infant immunization with conjugated polysaccharide vaccines can generate antibodies with a progressive avidity increase [26][27][28][29][30]. However, these studies do not allow the comparison of infant data with those obtained following the immunization of older children or adults, because the latter are already naturally primed by carriage or exposure to cross-reacting polysaccharides prior to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in infants indicated a progressive increase of somatic mutation of immunoglobulin genes between 2 and 10 months of age, with evidence for selection only observed from 6 months onwards [24,25]. Avidity maturation was shown to occur following early infant immunization with conjugated polysaccharide vaccines [26][27][28][29][30]. However, it has been reported that following N. meningitidis infection, infants produced specific antibodies of a significantly lower average avidity than older children, which correlated with the absence of bactericidal activity in infant sera [31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to measuring antibody responses, avidity maturation (which is characteristic of a T-celldependent antibody response) can be assessed after immunization with polysaccharide conjugate vaccines and then used as a surrogate marker for the induction of immune memory. The use of avidity indices (AIs) in this way has now been widely documented for MCC (4,19,20), Haemophilus influenzae type b (Hib) conjugate (9,16), and pneumococcal conjugate (2) vaccines.…”
mentioning
confidence: 99%